2017
DOI: 10.1186/s13148-017-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of sorbin and SH3 domain containing 3 (SORBS3) in human skeletal muscle following Roux-en-Y gastric bypass surgery

Abstract: BackgroundObesity is a disease that is caused by genetic and environmental factors. However, epigenetic mechanisms of obesity are less well known. DNA methylation provides a mechanism whereby environmental factors can influence gene transcription. The aim of our study was to investigate skeletal muscle DNA methylation of sorbin and SH3 domain containing 3 (SORBS3) with weight loss induced by Roux-en-Y gastric bypass (RYGB).ResultsPreviously, we had shown increased methylation (5.0 to 24.4%) and decreased gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…These changes after bariatric surgery were also associated with changes in the transcript levels, suggesting that these weight loss-induced epigenetic changes play a role in the regulation of metabolic gene transcription loss (88). A recent study demonstrated that weight loss induced by RYGB surgery is able to restored to normal levels the SORBS3 methylation and gene expression in the muscle (91). Alterations in the expression and methylation patterns of genes involved in insulin signaling as well as those related to specific non-alcoholic fatty liver disease (NAFLD) were also observed in liver biopsies after bariatric surgery (92).…”
Section: Changes In Epigenetic Marks After Bariatric Surgerymentioning
confidence: 99%
“…These changes after bariatric surgery were also associated with changes in the transcript levels, suggesting that these weight loss-induced epigenetic changes play a role in the regulation of metabolic gene transcription loss (88). A recent study demonstrated that weight loss induced by RYGB surgery is able to restored to normal levels the SORBS3 methylation and gene expression in the muscle (91). Alterations in the expression and methylation patterns of genes involved in insulin signaling as well as those related to specific non-alcoholic fatty liver disease (NAFLD) were also observed in liver biopsies after bariatric surgery (92).…”
Section: Changes In Epigenetic Marks After Bariatric Surgerymentioning
confidence: 99%
“…In skeletal muscle biopsies 6 mo after surgery, gastric bypass patients had normalized DNA methylation in 11 metabolic gene promoters, including PDK4, peroxisome proliferator-activated receptor γ coactivator 1 α (PPARGC1A), pyruvate dehydrogenase E1 α 1 subunit (PDHA1), myosin heavy chain 2 (MYH2), acyl-CoA oxidase 1 (ACOX1), and others (46). Another study found reduced methylation in skeletal muscle at 30 CpGs associated with sorbin and SH3 domain containing 3 (SORBS3) after Rouxen-Y gastric bypass surgery (47). In addition to muscle, DNA methylation profiles of omentum and subcutaneous adipose tissue were altered by gastric bypass surgery (48).…”
Section: Cr-induced Dna Methylation Changes and Immuno-metabolismmentioning
confidence: 99%
“…Improved metabolic performance was associated with an increase in PPARGC1A expression, resulting from a decrease in PPARGC1A promoter region methylation [57]. Another recent study found that sorbin and SH3 domain containing 3 (SORBS3) expression in skeletal muscle was regulated by the methylation of its promoter region, altered in obesity, and restored to normal levels through gastric bypass surgery-induced weight loss [58]. Previous studies found that SORBS3 gene expression was significantly associated with BMI, percent body fat, and fasting insulin and glucose levels [58].…”
Section: Effect Of Acute Weight Loss and Exercise On Dna Methylation mentioning
confidence: 99%
“…Another recent study found that sorbin and SH3 domain containing 3 (SORBS3) expression in skeletal muscle was regulated by the methylation of its promoter region, altered in obesity, and restored to normal levels through gastric bypass surgery-induced weight loss [58]. Previous studies found that SORBS3 gene expression was significantly associated with BMI, percent body fat, and fasting insulin and glucose levels [58]. Collectively, the post-surgery data furthered our understanding of changes in DNA methylation that is associated with obesity and T2D.…”
Section: Effect Of Acute Weight Loss and Exercise On Dna Methylation mentioning
confidence: 99%